RANK/RANKL/OPG LIGAND-RECEPTOR SYSTEM AND ITS ROLE IN PRIMARY BONE NEOPLASMS (LITERATURE ANALYSIS AND OWN DATA) - E. S. Gershtein; Yu. S. Timofeev; A. A. Zuev; N. E. Kushlinskii (Успехи молекулярной онкологии)
RANK/RANKL/OPG ligand-receptor system is a key player in bone homeostasis regulation directly regulating osteoclast differentiation and osteolysis. Disbalance of bone homeostasis associated with malfunctioning of RANK/RANKL/OPG system underlies such oncological processes as the destruction of bone, metastasis development, tumor progression. Involvement of RANK/RANKL/OPG system in the development of metastasis from various tumors is practically confirmed, but its influence on the development and progression of primary bone tumors still needs thorough evaluation. , In this paper experimental and clinical-laboratory data on the role of RANK/RANKL/OPG system in primary bone tumors pathogenesis available in modern literature are summarized with special attention,paid to giant-cell bone tumor (GCBT) that is already treated with RANK/RANKL interaction inhibitor denosumab. Results of authors study of the levels of RANK/RANKL/OPG system,s components in blood serum of 101 malignant bone tumor (37 – osteosarcoma, 41 – chondrosarcoma, 12 – chordoma, 7 – Ewing sarcoma, 2 – pleomorhic undifferentiated sarcoma, 2 – fibrosarcoma), 32 borderline GCBT, and 30 benign bone tumor patients are also presented. The disturbances in the balance of osteolysis activators and inhibitors in patients with primary bone tumor depending both on the character of neoplasm (malignant, borderline or benign), and histological structure of malignant tumors were demonstrated. The most striking changes in RANK/ RANKL/OPG system manifesting itself in an increase of serum concentrations of all its components and strengthening of association between the levels of soluble receptor and its natural inhibitor OPG were revealed in giant-cell bone tumor patients.The study of the role of RANK/RANKL/OPG system in primary bone neoplasms is a topical goal for clinical investigations; it is also a promising tool for development of new diagnostic methods and for targeted application of specific drugs inhibiting its activity.